PENERAPAN ALGORITMA ARI BORNEO (AB) UNTUK PEMBACAAN TEKS DENGAN MEMANFAATKAN MICROSOFT SPEECH DAN ID1 - Ari Restani; Anton Setiawan Honggowibowo; Yuliani Indrianingsih (Compiler, 2013)
Reading is an activity person to obtain information from something written. Reading involves recognition of the symbol and the letters that make a language. But there are some people who are lazy to read text in English language which is not a language that is used everyday by Indonesian people. In addition to reading, there are also the most common activities to obtain information that is heard. Hear is a way to gain an understanding of the meaning of the information in the form or sound using auditory senses. Reading activities contributed 10% ability for know information, with listening, knowing information can reach 30%. With conditions like this, then it needs an alternative media that can help treat the condition. The alternative media that can be made is text to speech fo r read text in Indonesia language and English language, for detection language using Ari Borneo Algorithm. These systems are made using Delphi 7 programming language, MBROLA Tools as Indonesia-speaking sound generators and Microsoft Speech API as English sound generator. Through this system, userscan absorb information from listening to the reading o f text by both systems.